2023
DOI: 10.1063/5.0157931
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-controlled chiral induced spin selectivity effect in ds-DNA

Abstract: In this research, we explore sequence-dependent chiral-induced spin selectivity (CISS) in double-stranded (ds)-DNA using time-correlated single-photon counting and electrochemical impedance spectroscopy supplemented by tight-binding calculations of the phenomenon for the first time. The average lifetime of the photo-excited electrons in a Quantum Dot-DNA system is influenced by the CISS effect generated by the DNA molecule, and the difference in average time decay of electrons was found to be 345 ps for opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The spin-specific change in charge transport through chiral molecules in electrochemical tunnel junctions, be that through monitoring changes in current or charge transfer rate, likely arise from the same phenomenon: spin-dependent changes in resistance for charge transport. This supposition is supported by recent impedance measurements made on DNA coated ferromagnetic electrodes, in which an equivalent circuit model analysis is used to extract the charge transfer resistance as a function of applied magnetic field. For the DNA assemblies, deviations in charge transfer resistance with magnetization orientation are observed, owing to the CISS effect; however, in achiral systems the charge transfer resistance is unaffected by the magnetic field orientation.…”
Section: Methods For Measuring Cissmentioning
confidence: 88%
See 1 more Smart Citation
“…The spin-specific change in charge transport through chiral molecules in electrochemical tunnel junctions, be that through monitoring changes in current or charge transfer rate, likely arise from the same phenomenon: spin-dependent changes in resistance for charge transport. This supposition is supported by recent impedance measurements made on DNA coated ferromagnetic electrodes, in which an equivalent circuit model analysis is used to extract the charge transfer resistance as a function of applied magnetic field. For the DNA assemblies, deviations in charge transfer resistance with magnetization orientation are observed, owing to the CISS effect; however, in achiral systems the charge transfer resistance is unaffected by the magnetic field orientation.…”
Section: Methods For Measuring Cissmentioning
confidence: 88%
“…DNA (see refs , , , , , , , ) and α-helical oligopeptides (see refs , , , , , , , , , , , , , , , , , ) have been widely used to explore the CISS effect and its connection with molecular properties. Having been investigated by spin-dependent photoemission, transport, electrochemical, and spin-dependent polarization experiments, they comprise testbed systems for comparisons between methods.…”
Section: Materials and Molecules Exhibiting Cissmentioning
confidence: 99%
“…15 In our recently published work, we investigated sequence-specific spin selectivity through several dsDNA using time-correlated single-photon counting (TCSPC) measure-ments. 16 It was observed that there exists an asymmetry in the average decay lifetime of excitons for two directions of the magnetic field due to the CISS effect which (differential average lifetime) reduced to approximately 83% with a point mutation in DNA. Note that besides DNA, achiral and chiral quantum dot assemblies show different average decay lifetimes when excited with clockwise (CW) and counterclockwise (CCW) circularly polarized light for either L-or D-cysteine-coupled quantum dots.…”
mentioning
confidence: 99%
“…The PL decay curves of QD-DNA were fitted by a three-exponential function. The equation is given by , I ( t ) = prefix∑ i = 1 3 A i normale t / τ i where t is time and A i is the weighting parameter associated with each decay time. An average amplitude-weighted lifetime is defined as τ = prefix∑ i = 1 3 A i τ i 2 A i τ i The nonradiative average decay lifetime of optically excited states for the QD-ssDNA system was calculated using eq and was found to be ∼8.98 ± 0.4 and ∼8.82 ± 0.4 ns for the magnetic field in the “UP” and “DOWN” directions, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation